Easy Formation of Functional Liposomes in Water Using a pH‐Responsive Microbial Glycolipid: Encapsulation of Magnetic and Upconverting Nanoparticles. Issue 9 (12th July 2019) - Van Renterghem, Lisa; Guzzetta, Fabrizio; Le Griel, Patrick; Selmane, Mohamed; Messaoud, Ghazi Ben; Tan Su Teng, Tabitha; Lim, Sierin; Soetaert, Wim; Roelants, Sophie; Julián‐López, Beatriz; Baccile, Niki
Abstract: The compartmentalization of colloids into topologically closed, vesicular, microphases offers an attractive mean to concentrate a functional cargo in aqueous solutions for a range of biomedical, cosmetic, and biotechnological applications. In this paper, we develop a simple, phospholipid‐free, phase change method employing a pH‐responsive glycolipid. The method is applied to the encapsulation of a sonicated, metastable, aqueous dispersion of functional colloids in the lumen of lipid vesicles: uncoated magnetic maghemite γ‐Fe2 O3 and oleic‐acid coated upconverting NaYF4  : Yb/Ln (Ln=Er or Tm) nanoparticles (NPs). We find a stable liposomal dispersion containing a sub‐population of crowded liposomes with high concentrations of NPs. The encapsulated NPs, formed at nearly neutral pH and room temperature, are stable over time and towards extrusion. The vesicular microphase is entirely composed of pH‐responsive glycolipids, which undergo a pH‐mediated mesoscopic structural transition from an open lamellar (24). We also show that encapsulation successfully works with a stable colloidal aqueous dispersion of iron clusters stabilized in ferritin cages. This compartmentalization approach combining self‐assembly with an orthogonal nonequilibrium dispersion of nanoparticles shows untapped potential for synthesizing unusual classes of mixed matter. Abstract : Bulk encapsulation of (coated or hydrophobic) nanoparticle aggregates into vesicles is possible by a simple lamellar‐to‐vesicle phase transition above pH 4 by using only a pH‐responsive microbial glucolipid. The encapsulation spontaneously occurs in bulk water, without solvents or phospholipids. The process is developed with iron oxide nanoparticles to form magnetoliposomes but is extended to the encapsulation of upconverting nanoparticles with an average encapsulation efficiency of 60%.